(3HMGQ GdCfhGQ GdLGeYI dOQQ CNHGQ GdCFeI GdCWgGQs - (3GdCUagGfj, GdeLdSj, eMeO HGbQ Hf eMeO Jbj Hf ebUhO Ydj, J(B1111(3g`s ((3GHf eMeO eMSf eMeO ebje CHgQjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj Rjf SeGA GdOjf HGdTeS hGdbeQ(B...(3CeG HYO agPG gh GdeLdO GdKGfj YTQ(B...(3CHhGH JGQjN GdEeGe GdQJLi(B...(3CHj GdMSf Ydj Hf ehSi GdQVi(B...s
(3BNQgG (B:s
...(3hNQLJ Ce CHj eMeO Ydjg GdSdGe Edi ecI hbHV Ydjg GdSdGe aj aj TgQ QHjY GdBNQ SfI SJjf heGFJjf hOaf(B...(3Edi LGfH CHjg(B...s
(3fSNI aj MjGI GdeDda, hbO CJe GdeDda cJGHJgG aj (B17 (3Pj GdMLI (B1077(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B48s
(3GdPQjYI(B:(3L(B3(3,U(B11(3,Qbe(B43s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdMOjK hGdeUWdMs